How to deal with LM Disease in NSTEMI patient: PCI or CABG? - Lutfi Hafiz Zunardi; Mohammad Saifur Rohman; Budi Satrijo; Adriawan Widiya Nugraha (Heart Science Journal, 2023)
Â Background: The left main coronary artery (LMCA) with acute coronary syndrome have been associated with significant morbidity and mortality. Urgent CABG is recommended for patients with LM disease accompanied by ACS, but requires special preparation and adequate facilities. not all hospitals are ready. PCI on left main coronary artery is a high risk procedure which requires special preparation like IVUS and FFR. Meanwhile, the ACS case is an emergency that needs to be treated immediately. Interventional management is mandatory in this setting, but the concern is whether the action is carried out in an emergency or an elective procedure.Objective: This study aimed to describe the management of LM disease in NSTEMI patients.Case presentation: We will discuss a 69-year-old male brought to our hospital because of chest pain while doing moderate activity. The patient was previously referred from a private hospital and was assessed asÂ NSTEACS. from angiography there was Stenosis dd Thrombus at LM, the cardiologist suggest him to be referred to RSSA for CVCU admission and will be underwent Urgent revascularisation. Clopidogrel and aspirin were routinely consumed as dual antiplatelet therapy. We treat the patient with an unfractionated heparin (UFH) bolus, continued with continuous infusion until revascularization. No event of subsequent acute coronary syndrome was observed.Conclusion: Although the management of patients with LM disease requires some preparation before action is taken, urgent revascularization in Acute coronary syndrome cases must still be carried out immediately.